2019
DOI: 10.1371/journal.pone.0210255
|View full text |Cite
|
Sign up to set email alerts
|

Do government expenditure and financial development impede environmental degradation in Venezuela?

Abstract: Environmental degradation is causing global warming, which is of the utmost concern to both physical and social scientists. A number of potential determinants of environmental degradation are analysed in the literature. This study examines the role of government expenditure and financial development in environmental degradation in the context of the environmental Kuznets curve (EKC) hypothesis for the Venezuelan economy. Time series data have been analysed for this purpose. The long-term relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The Cobb–Douglas is a production approach that is widely used as an apt tool to find relations between production and economic factors: where and are the elasticities of Y vis-à-vis L and PKS . Therefore, from the extended Cobb–Douglas production function, it is assumed that the levels of government finance expenditure [ 17 , 18 , 75 ] capital K it = GEX it in the model, which includes CO 2 proxying EQ, which is extended as: where CO 2 it and GEX it of country i and time t in years. Here and are the elasticities of output.…”
Section: Data and Variablesmentioning
confidence: 99%
“…The Cobb–Douglas is a production approach that is widely used as an apt tool to find relations between production and economic factors: where and are the elasticities of Y vis-à-vis L and PKS . Therefore, from the extended Cobb–Douglas production function, it is assumed that the levels of government finance expenditure [ 17 , 18 , 75 ] capital K it = GEX it in the model, which includes CO 2 proxying EQ, which is extended as: where CO 2 it and GEX it of country i and time t in years. Here and are the elasticities of output.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Mohammed et al [18] studied the effects of energy, financial development, and government expenditure on carbon emissions in Venezuela. This study found that variables of the study were in the long run relationship, and the long run estimates showed that the EKC hypothesis holds in Venezuela.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green tax causes many industrialists to employ production techniques that cause less harm to the environment. López et al ( 2011 ) explain that government spending oriented on public and social goods reduces pollution because it leads to human capital that affects environmental quality positively whereas Mohammed Saud et al ( 2019 ) are of the view that government expenditure can affect the environment through three effects, that is, scale, composition and technical and the first effect results in environmental degradation while other two effects put a positive impact on the environment. The projects on water and sanitation may improve access to a clean environment for the deprived section of the economy, while green tax promotes energy-efficient technology and discourages deforestation.…”
Section: Methodology For the Construction Of Environmental Inclusionmentioning
confidence: 99%